Maintaining Mental Health for Javanese People in Retirement - Bratajaya, Alissa Dian; Triratnawati, Atik (Indonesian Journal of Medical Anthropology, 2023)
In the elderly age category, a person can no longer be called productive and generally has entered retirement age. Changes during retirement usually happen in a relatively short time, so without the right strategy to deal with these changes, they can cause health problems, especially mental health problems. This paper will discuss the changes that occur in retirees and how these retirees deal with the changes that occur. This paper uses a qualitative method with a phenomenological approach to explain the experiences of each individual in facing retirement. This research was conducted in August and October-November 2022 in the city of Yogyakarta area using a purposive sampling method and got five retirees as informants. Apart from interviews with retirees, some of the retiree’s families were also interviewed to obtain a complete data. The most prominent changes in the lives of the elderly are in the economic and social fields. Economic changes occur due to reduced income and health problems. Changes in social aspects reduced activity, reduced social contact, and loss of facilities. Retirees face these changes by preparing savings, opening businesses, pursuing hobbies, and participating in community activities.